First Report of Hepatozoon procyonis in Raccoons from Costa Rica - Meneses, Ana (2016)
This study reports for the first time the detection of Hepatozoon procyonis in raccoons, Procyon lotor from Costa Rica. Blood smears of naturally infected raccoons were taken to characterize the gametocytes. Gametocyts consistent with Hepatozoon procyonis were observed in the cytoplasm of neutrophils, and their morphology, which is similar to the one reported in raccoons throughout the Americas, is described.